Performance of zeolite powder and tubular membrane having different Si/Al ratio for removing As(III) in aqueous phase. Issue 3 (11th February 2017) - Roy, Priyanka; Pal, Pameli; Sensharma, Sudendu; Das, Nandini; Bandyopadhyay, Amitava
Abstract: Three different types of zeolite having pore sizes in the range 0.26‐0.74 nm, (NaP, NaA, and NaY) powders and membranes are synthesized with different Si:Al ratio on low cost clay alumina tubular support. The results of the permeation and separation studies showed that the NaP zeolite powder and membrane removes maximum As(III) from the water solution (more than 80%) compared to other zeolites. The removal of As(III) to achieve drinking water standard, by zeolite membrane, in a single step process does not seem to have been reported before the present investigation. These are the novelty achieved.